Analisis Pengelolaan Surat Masuk Dan Peran Subbagian Keuangan, Umum Dan Logistik Pada Kantor Komisi Pemilihan Umum (KPU) Kota Tangerang - Saputri, Dwi Azizah; Dippo Alam (Al-Zayn : Jurnal Ilmu Sosial & Hukum, 2026)
This study aims to analyze the management of incoming mail and the role of the Finance, General Affairs, and Logistics Subdivision at the Komisi Pemilihan Umum (KPU) of Tangerang City. The research uses a qualitative approach through literature review and interviews. The results show that incoming mail management has been carried out through the stages of receipt, recording, registration, and disposition. However, obstacles occur in handling urgent letters due to the absence of leadership, which causes delays in follow-up actions. Therefore, optimization is needed through delegation of authority, the use of digital systems, improved coordination, and the development of standard operating procedures (SOPs) to enhance effectiveness and efficiency.